Validity of Export-Led Growth Hypothesis in the Nigeria Oil And Non-Oil Exports: Evidence from Ardl and Causality Test Approaches - OGUNYOMI-OLUYOMI, Oluwatosin Olatunji; AKINYOMI , Oladele J.; OLAMADE, Olumuyiwa O. (Acta Universitatis Danubius. Œconomica, 2023)
Numerous studies have tested the validity of the export-led growth hypothesis, yet, fewer studies have considered the disaggregated exports into oil and non-oil exports-growth nexus and also test whether oil and non-oil exports cause economic growth in the literature. Therefore, this study tests the validity ofthe export-led growth hypothesis in Nigeria's oil and non-oil exports over the study period of 1970 to 2021. In line with the specific objectives of this study, autoregressive distributed lag (ARDL) and Granger causality tests were employed to estimate the short-run and long-run export-growth relationship as well as test the validity of the export-led growth hypothesis respectively. Annual secondary data was employed for this study. Results of this study found that oil exports and non-oil exports have negative and positive significant effects on economic growth in the short run and long run at 1% and 10% respectively. Furthermore, the findings revealed that the export-led growth hypothesis (ELGH) is not valid because the unidirectional causal relationship between oil and non-exports to economic growth was not statistically significant in Nigeria. Lastly, the study recommends the need to intensify the exports drive policies to improve and strengthen the oil exports and non-oil export sectors that will cause economic growth in the country, Nigeria.